Assessment of Gait Therapy Effectiveness in Patients with Parkinson’s Disease on the Basis of Three-Dimensional Movement Analysis - Mirek, Elżbieta; Kubica, Jadwiga Lubomira; Szymura, Jadwiga; Pasiut, Szymon; Rudzińska, Monika; Chwała, Wiesław (Frontiers in Neurology, 2016)
Objective The aim of this study was to assess the effect of physical exercise on gait pattern disorders, based on three-dimensional gait analysis in the sagittal plane in a group of people with Parkinson’s disease (PD). Methods Thirty-two subjects with PD (14 women and 18 men; age: 50–75 years) were qualified for the study, which ran for 3 weeks and included 18 therapeutic sessions. Thirty-five control subjects were included in the research (13 women and 19 men; age: 52–77 years). Gait analysis using the Vicon 3D system took place in the Biokinetics Laboratory. The research group was tested before and after treatment, and the control group was tested once. Results Comparing the average peak angle changes and average standard time results (% gait cycle) corresponding with angles of movement in the lumbar spine, cervical spine, elbow joint, and shoulder joint, statistically significant changes were observed. The study results are indicative of differences in spatiotemporal parameters and angular changes in gait for both groups. After therapeutic treatment, we observed improvement in the angular range of changes in thorax tilting, but there were no difference between the most affected and less affected side. For the cervical spine, a significant reduction in flexion during dual support was observed. The angular range of changes in shoulder joint was significant only in less affected shoulder during the initial contact (F1), terminal stance (F4), and terminal stance (F8) phases of gait (p < 0.05). After therapeutic treatment, significant angle and setting changes in the most affected limb of the elbow joint occurred during the initial contact and terminal swing phases (F1, F8). In the terminal stance phase (F4), an increase in range of motion by about ±4° was observed (p < 0.05). Conclusion Exercise therapy slightly increased the range of movement in the examined joints of PD’s patients. Results of pathological walking patterns occurring prior to treatment improved after treatment and moved closer to the physiological gait pattern.